(untitled) (Global Journal of Human-Social Science, 2024)
This paper seeks to establish a pioneering methodological framework for reconstructing the life story of Princess Anna Maria Morso Bonanno As the spouse of Ignazio Patern Castello the fifth prince of Biscari Anna s life has not been adequately explored within historical scholarship This study uses a digital history methodology to illuminate the Princess s role within the Biscari family s social network by analyzing a series of letters housed in the Biscari Archive This investigation endeavours to reevaluate her status within the Sicilian nobility emphasizing her strategic participation in the feudal system and her governance capabilities Ultimately this approach aspires to underscore the influence of women in the management of power thereby enriching a historiography that has predominantly concentrated on male figures